Identificação e expressão recombinante de um novo peptídeo de potencial antimicrobiano derivado da proteína de reconhecimento de Peptidoglicanos 3 humana - Laprega, Pedro Mendes (Universidade Federal de São Carlos, 2024)
During the 21st century, bacterial resistance to drugs has reached dangerous levels, necessitating the development of new therapeutic strategies to combat these pathogens. Among them, antimicrobial peptides (AMPs) emerge as promising candidates, as they often have mechanisms of action distinct from conventional antibiotics, targeting various components of the bacterial membrane, leading to its disruption. Furthermore, due to well-described physicochemical characteristics and advances in computational resources, various in silico strategies have been developed for the identification and design of these compounds. In this study, we proposed the identification of a new potential antimicrobial peptide through computational mining of the human proteome, followed by its recombinant production. During our analyses, we identified a promising candidate derived from Peptidoglycan Recognition Protein 3 (PGLYRP3), hence named AMP-PGLYRP3. The identified AMP was predicted, through in silico analyses, to be a cationic, amphipathic peptide with an alpha-helical structure, characteristics well-described in antimicrobial peptides. Additionally, AMP-PGLYRP3 showed no hemolytic or allergenic potential, suggesting possible therapeutic applications. The peptide was expressed in a baculoviral system using the SUMO3 fusion protein. Finally, in vitro tests of the peptide's activity will be conducted to validate the results obtained from our analyses, advancing the development of this therapeutic candidate.
Identification and recombinant expression of a new potential antimicrobial peptide derived from de human Peptidoglycan recognition protein 3
Keywords: Peptídeo antimicrobiano; Antimicrobial peptide; Proteína de reconhecimento de peptifoglicanos 3; Peptidoglycan recognition protein 3; Expressão heteróloga; Heterologous expression; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR